2012
DOI: 10.5581/1516-8484.20120104
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Practices Committee of a public blood bank network in Minas Gerais, Brazil

Abstract: ObjectiveThis study aimed to verify the performance of blood transfusion committees in transfusion services linked to the public blood bank network of the state of Minas Gerais. MethodsA cross-sectional observational study was conducted between 2007 and 2008 using questionnaires and proficiency tests to evaluate the reporting and investigation of transfusion reactions comparing transfusion services with and without transfusion committees in the public transfusion services of the state of Minas Gerais. ResultsN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Hospital blood transfusion committees have also been established in other countries, such as Brazil, where they are present in 63.4% of blood transfusion services. 10 In a survey conducted in the Netherlands in 2012, all 76 hospitals were found to have HTCs. 11…”
Section: Discussionmentioning
confidence: 99%
“…Hospital blood transfusion committees have also been established in other countries, such as Brazil, where they are present in 63.4% of blood transfusion services. 10 In a survey conducted in the Netherlands in 2012, all 76 hospitals were found to have HTCs. 11…”
Section: Discussionmentioning
confidence: 99%
“…A Agência Nacional de Vigilância Sanitária informou que, no ano de 2011, ocorreram 5.340 reações transfusionais, com uma subnotificação estimada de 50,1% (22) . Estudo realizado em 226 centros de sangue do núcleo de hemoterapia e agências transfusionais em 178 municípios do estado de Minas Gerais, Brasil, concluiu-se que a incidência de notificação e investigação das causas de reações transfusionais foi maior nos serviços de transfusão que possuíam comitê transfusional atuante, embora, no geral, o desempenho dos comitês de transfusão tenha sido considerado incipiente, carente de melhores formas de organização (23) . No caso dos participantes deste estudo, por terem sido submetidos a inúmeros procedimentos invasivos e pela necessidade de continuidade de tratamento pós-operatório de cirurgia cardíaca, o processo transfusional possui forte significado, uma vez que dele depende a qualidade de suas vidas.…”
Section: Reconhecimento Do Processo Transfusional (Ic) Tem Certas Hounclassified
“…The authors of this study concluded that, the incidence of notification and investigation of the causes of transfusion reactions was higher in transfusion services where a transfusion committee was present. However, despite these results, the performance of transfusion committees was found to be incipient and better organization and effectiveness are required (19) .…”
mentioning
confidence: 99%